1987
DOI: 10.1177/028418518702800312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endoscopic Retrograde Pancreatography with Functional and Histologic Changes in Chronic Pancreatitis

Abstract: The findings from endoscopic retrograde pancreatography (ERP) and secretin-CCK test data were compared in 69 patients: 36 with chronic pancreatitis, 9 with possible chronic pancreatitis, and 24 without chronic pancreatic disease. The ERP findings were also compared with the histologic changes in pancreatic tissue in 18 patients who underwent pancreatic surgery for chronic pancreatitis. ERP films were reviewed according to the criteria proposed by KASUGAI et coli. (8) with special attention paid to the side bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, imaging or function tests may not reveal early chronic pancreatitis, and their results do not necessarily correlate with each other. [4][5][6][7][8]14 However, pancreatic function tests are commonly performed if pancreatic disease is possible. The simplest noninvasive tests measure exocrine pancreatic enzymes in blood samples.…”
Section: Current State Of Chronic Pancreatitis Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, imaging or function tests may not reveal early chronic pancreatitis, and their results do not necessarily correlate with each other. [4][5][6][7][8]14 However, pancreatic function tests are commonly performed if pancreatic disease is possible. The simplest noninvasive tests measure exocrine pancreatic enzymes in blood samples.…”
Section: Current State Of Chronic Pancreatitis Diagnosismentioning
confidence: 99%
“…Furthermore, imaging or function tests may not reveal early chronic pancreatitis, and the results of these tests do not necessarily correlate with each other. [4][5][6][7][8] The quest continues for useful biological and functional markers of early-stage chronic pancreatitis. 9 Recently, chemokines have come to be known as an important factor in the progression of chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47] It is suggested that if only one of the examinations such as those listed in Table 3 had been performed, the diagnosis would have been missed in approximately 20% of cases. 47,48 Indeed, the second Marseilles symposium concluded that pancreatic function testing and imaging procedures complement each other, and that a grading system based on both types of procedures may provide an important diagnostic advantage and should be prospectively investigated.…”
Section: Problems With the Jps Criteria 2001 For The Diagnosis Of Chrmentioning
confidence: 99%
“…63,64 Other older comparisons with histologic findings found a similarly modest sensitivity. 65,66 Fecal elastase has a sensitivity of 45% to 63% for mild disease but 73% to 100% for severe 67-69 disease compared with ERCP 67 or invasive pancreatic function tests. 68,69 Studies of MRCP have shown that the main pancreatic duct is seen well, especially with secretin, although resolution of side branches is inferior compared with ERCP.…”
Section: Reference Standards and Competing Technologiesmentioning
confidence: 99%